Detection of ionospheric perturbation after Northern Sumatra earthquake on 26 December 2004 - Ho, Yih Hwa; Zain, A.F.M (2005)
The Earth ionosphere variations are considered after tsunami associated with the long-period Rayleigh waves occurred December 26, 2004 in Indonesia (Ms = 9.0). In this paper we focus on the relative variations in ionospheric parameters (total electron content (TEC) and scintillation parameter, S4) with respect to a quiet period. Differential ionospheric parameters were made by computing the percent change of seismic-time parameter relative to ionospheric parameters computed for quiet conditions.